Leaf water relations and structural traits of four temperate woody species occurring in serpentine and non‐serpentine soil. Issue 4 (17th May 2019) - Kawai, Kiyosada; Saito, Haruka; Kajino, Hirofumi; Nakai, Wataru; Nakamura, Ryosuke; Sato, Kai; Okada, Naoki
Abstract: Low water‐holding properties impose dry conditions on plants on serpentine soil. To test the hypothesis that leaf water relations are key plant characteristics to grow in serpentine soil, we compared these traits for four tree species ( Quercus serrata, Clethra barbinervis, Magnolia obovata and Pieris japonica ) growing in serpentine soil and brown forest (BF) soil. Despite a much lower soil moisture content, trees in the serpentine soil (S) plot showed similar predawn leaf water potential to trees in the BF plot in all species. Trees in the S plot showed higher drought tolerance or drought avoidance than trees in the BF plot. In the S plot, enhanced drought tolerance through osmoregulation was observed in Q. serrata and P. japonica, whereas decreased leaf capacitance was observed in C. barbinervis and Q. serrata . Decreased stomatal conductance, a typical way to avoid drought stress, was observed for serpentine C. barbinervis and M. obovata and midday leaf water potential was comparable between S and BF plots for C. barbinervis . Lamina dry mass per area was higher for C. barbinervis but lower for Q. serrata in the S plot. Wood density was higher in serpentine Q. serrata and M. obovata . On the other hand, all studied species showed lower leaf nitrogen concentration in the S plot. Our results suggest that (a) despite low water availability, the tress in the serpentine plot did not suffer drought stress, and (b) leaf water relations may be one of the traits that enabled trees to inhabit serpentine soil. Abstract : We suggest that (1) despite low water availability, the tress in the serpentine plot did not suffer drought stress, and (2) leaf water relations may be one of the traits that enabled trees to inhabit serpentine soil.